Subsequent IVF outcomes following antibiotic therapy for chronic endometritis in patients with recurrent implantation failure. Issue 12 (21st September 2021) - Demirdag, Erhan; Guler, Ismail; Cevher Akdulum, Munire Funda; Sahin, Esin; Erdem, Ozlem; Erdem, Ahmet; Erdem, Mehmet
Abstract: Aim: The aim is to identify the chronic endometritis (CE) incidence in recurrent implantation failure (RIF) patients undergoing in vitro fertilization (IVF) treatment and compare the IVF outcomes of RIF patients with CE following antibiotic therapy with RIF patients without CE. Another purpose is to compare the IVF outcomes of described RIF patients with patients undergoing the first cycle of IVF. Methods: In this retrospective cohort study, CE was diagnosed with CD‐138 immunohistochemical staining. Among RIF patients, two groups were formed as group 1, including patients diagnosed with CE and treated by antibiotics ( n = 129), and group 2, including patients without CE ( n = 103). Patients with the first IVF cycle having similar infertility etiologies with RIF patients were reviewed as group 3 ( n = 932). Results: CE was diagnosed in 55.6% of RIF patients. The number of oocytes retrieved was not different between groups. Implantation rates (IR) were similar after antibiotic treatment in RIF patients with or without CE. However, Group 3 had a higher IR (41.1%) than group 1 and 2 (23.1% and 30.1%, respectively) ( p < 0.001). Clinical pregnancy (CPR) and live birth rates (LBR) were comparable between RIF groups. However, CPR and LBR were significantly higher in group 3 (48.6% and 40.5%) than group 1 (36.4% and 27.9%), and group 2 (37.9% and 30.1%) ( p = 0.007 and p = 0.005, respectively). Conclusion: Unidentified endometrial factors except CE may also affect the implantation process, although CE is a frequent finding in patients with RIF. Reproductive outcomes may not be improved only with antibiotics in RIF patients with CE.